Complete Genomic Data of Burkholderia glumae Strain GX Associated with Bacterial Panicle Blight of Rice in China - Wang, Sai (Plant disease, 2020)
Burkholderia glumae is a seedborne pathogen causing bacterial panicle blight of rice. Here, we report the complete genome of B. glumae strain GX, which represents the first whole-genome sequence of an isolate from China. The assembled genome consisted of five contigs, with two circular chromosomes of 3,712,850 and 2,750,046 bp and three plasmids of 201,571, 105,587, and 96,100 bp. This complete genome will provide a valuable resource for further studies on bacterial panicle blight worldwide